2021
DOI: 10.1177/0958928720973912
|View full text |Cite
|
Sign up to set email alerts
|

When free choice turns into a pitfall: conditional social protection for immigrants in voluntary unemployment insurance systems

Abstract: Unemployment insurance systems are designed to provide income security for those who drop out of work temporarily. This form of social protection is particularly relevant for foreign-born workers who are, on average, more likely to become unemployed during layoffs. The article explores how the social protection of immigrants differs in cases where payments are tied to voluntary rather than mandatory contributions. This is done by focusing on a recent welfare reform in Sweden which led to both a sharp increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…The findings suggested that there was, in particular, a significant increase in incidence rates of hospitalisation due to alcohol-related disorders among unemployed individuals who were Swedish-born (regardless of whether they had Swedish-born or foreign-born parents), had low educational level, or were men. In terms of ethnic background, we initially hypothesised that the effect might be more pronounced among foreign-born individuals due to their overall weaker labour market attachment and, in particular, higher drop-out rate from the unemployment insurance funds [ 16 , 17 ]. This initially appeared to be the case for European foreign-born individuals whereas the opposite was found for the non-European foreign-born.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings suggested that there was, in particular, a significant increase in incidence rates of hospitalisation due to alcohol-related disorders among unemployed individuals who were Swedish-born (regardless of whether they had Swedish-born or foreign-born parents), had low educational level, or were men. In terms of ethnic background, we initially hypothesised that the effect might be more pronounced among foreign-born individuals due to their overall weaker labour market attachment and, in particular, higher drop-out rate from the unemployment insurance funds [ 16 , 17 ]. This initially appeared to be the case for European foreign-born individuals whereas the opposite was found for the non-European foreign-born.…”
Section: Discussionmentioning
confidence: 99%
“…Such funds generally have a higher representation of individuals with lower educational attainment and occupations generating less income, as well as foreign-born. Indeed, studies show that those who had resided in Sweden for a short period of time and originated from countries that are geographically far from Sweden were considerably more likely to drop out of the unemployment insurance funds [ 17 ]. Additionally, incentives for accessing the income-based scheme are most likely weaker among individuals with low income [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unemployment insurance was designed to alleviate the hardship of unemployment. Until the recent COVID-19 pandemic there was a trend towards reducing unemployment insurance generosity across the OECD ( Biegert, 2017 ; Gschwind, 2021 ; OECD, 2018 ). This was partly premised on findings that generous unemployment benefits extend unemployment duration ( Mortensen, 1976 ; for an overview see: Schmieder and Von Wachter, 2016 ).…”
Section: Introductionmentioning
confidence: 99%